(untitled) (American Journal of Islam and Society, 2013)
While much of the literature related to women and democratization in the Middle East neglects the role of women in this process, Wanda Krause persuasively argues that the grassroots activism of Middle Eastern women plays a vital role in democratizing the region. Krause contends that this scholarly neglect is a result of the literature’s (1) prioritizing the state (over civil society) and secularism (over religious groups), (2) ignoring the feminine (at the expense of the feminist) and the practical (at the expense of the political), and (3) relegating women’s concerns, like family issues, to “the private sphere and overlooked as having any meaning to the public” (p. 49). She further criticizes this literature for what she considers its orientalist attitude, which often manifests itself as excessive attention to women’s dress, segregation, polygamy, and female genital mutilation (FGM) and thus constructs a passive and oppressed image of Muslim women. To fully understand the role of Middle Eastern women, Krause urges scholars to focus not just on the government’s formal structures, but also to pay attention to civil society and investigate how beliefs, values, and everyday practices both expand it and advance democratic values ...